Modelo para la gestión turística local sostenible vinculado a la Escuela Superior Politécnica Agropecuaria de Manabí “Manuel Félix López” - Romero Donoso, Diana Patricia (2016)
The main objective of this research was to design a model for sustainable local tourism management linked to Escuela Superior Politécnica Agropecuaria de Manabí “Manuel Félix López”, in order to promote the development of tourism in Bolívar canton. The research is presented in four phases: tourist diagnosis, linking of the university processes to the local tourism planning, design and development of indicators and evaluation criteria. Results of an institutional linkage project carried out in Bolívar canton are presented. In the diagnosis the object of study was characterized from several perspectives: environmental, social, cultural, economic and political-institutional. The needs of the local community and tourism ventures were evaluated through technical visits, interviews and surveys; further supplementary information was obtained from institutional plans. The structure and organization of the system was determined by coordinating the dynamics and functioning of the departments involved consistently through two subsystems (GAD Bolívar and ESPAM MFL) that are invigorated, link, communicate and promote through their components and predetermined activities. Evaluation indicators to ensure the control and monitoring of management were proposed. It was shown that establishing a strategic link between GAD Bolívar and ESPAM MFL, is of great importance for local development and it is essential to involve communities and tourism entrepreneurs to ensure sustainability in management.